2021
DOI: 10.15261/serdj.28.11
|View full text |Cite
|
Sign up to set email alerts
|

Axial Mixing in Emulsion-flow Column under Iodine Extraction

Abstract: Strength of axial mixing in the emulsion phase during the progress of extraction was evaluated using the Peclet number under various flow conditions. The Peclet numbers were determined with the established tracer technology which applies inert species for iodine extraction. Very little effect of operating velocities of either aqueous and organic phases was found on the Peclet numbers. This fact indicates that an almost constant degree of axial mixing was kept in this column for different flow velocities of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Therefore, iodine transferred only in the organic phase. Since Hirayama et al [11] reported that the degree of axial mixing in the emulsion-flow column was comparable to that in packed column extractors, an assumption of counter-current plug flow regime was made for the flow condition of two phases. On the plug flow condition, iodine mass-transfer capacity coefficient, k o a, was determined by the following equation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, iodine transferred only in the organic phase. Since Hirayama et al [11] reported that the degree of axial mixing in the emulsion-flow column was comparable to that in packed column extractors, an assumption of counter-current plug flow regime was made for the flow condition of two phases. On the plug flow condition, iodine mass-transfer capacity coefficient, k o a, was determined by the following equation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Figure 9 shows a comparison between calculated values equations (7 and 8) and observed iodine concentration, x A . In calculation, Pe was set at 4 in accordance with the report by Hirayama et al [11].…”
Section: Iodine Concentration Distribution Along Column Heightmentioning
confidence: 99%